If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8 = a + a + 6 Reorder the terms: -8 = 6 + a + a Combine like terms: a + a = 2a -8 = 6 + 2a Solving -8 = 6 + 2a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-2a' to each side of the equation. -8 + -2a = 6 + 2a + -2a Combine like terms: 2a + -2a = 0 -8 + -2a = 6 + 0 -8 + -2a = 6 Add '8' to each side of the equation. -8 + 8 + -2a = 6 + 8 Combine like terms: -8 + 8 = 0 0 + -2a = 6 + 8 -2a = 6 + 8 Combine like terms: 6 + 8 = 14 -2a = 14 Divide each side by '-2'. a = -7 Simplifying a = -7
| 9x-13x=28 | | 14x+6= | | 5y(y-9)=0 | | 17-5k=2 | | 5=-3a-7 | | 39-n=5n-3(8+5n) | | 2y-10=18 | | 4(18-1)=2(18+7) | | 7-6x=4y | | 4x-2x=3+7 | | -18=2m-68 | | 86=5(x+8)+6 | | 4(36-1)=2(36+7) | | 91=2x+7x+1 | | xb+z=m-2x | | 4(5-1)=2(5+7) | | 15-3.2(6.8125)=-6.8 | | X-(4x-7)=5x-(x+2) | | 4(x-2)=-2(3-3x) | | 5x-6-7=x+6+x | | (-4x+6)+(6x-10)=0 | | 4(9-1)=2(9+7) | | -(k-12)=48 | | 4(9-1)=2(x+7) | | bx+z=m-2x | | 8y=-8x-16 | | 3x+4-x=-24 | | 27=-3-5b | | 6x-4(2x-5)=32 | | -2=-5x+2x+10 | | 4(x-1)=2(c+7) | | 3x+6+25+x+55+35=75 |